Assessing the Relation between Organization Climate and Job Nature with Staffs' Job Motivation in Isfahan Hospitals (Tehran University of Medical Sciences, 2015)
Background: Staffs' Job motivation is one of the most important factors in goals achievement in organization. As a result, considering effective factors of staffs' motivation is one of the main tasks of organization managers. The aim of current study is to assess the relation between organization climate and job nature with staffs' job motivation in Isfahan hospitals. Materials and Methods: this study was a descriptive and correlation one. The study population included all staff of total Hospitals in Isfahan city. The Sample size was estimated to 141based on Cochrane. Three questionnaires including organization climate, Job nature and job motivation were used. Data analysis was performed by SPSS software version16 using Pearson correlation coefficient test, linear regression, one- way ANOVA and LSD tests. Result: the study result revealed a significant positive correlation relation between organizational climate and job motivation (0.42), and Job nature and job motivation (0.36) (P<0.01). Furthermore, organizational climate (0.18) and Job nature (0.13) are predictors of f job motivation. One-way ANOVA test indicated there were significant statistical differences between job motivation and employment. Conclusion: With regard to the impact of organizational climate and Job Nature in job motivation, managers should pay more attention to these two valuable factors.